2014
DOI: 10.1186/1756-3305-7-364
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal analysis of sandfly fauna (Diptera: Psychodidae) in an endemic area of visceral leishmaniasis at Pantanal, central South America

Abstract: BackgroundEnvironmental changes caused by urbanization can cause alterations in the ecology and behavior of sandflies and in the epidemiology of leishmaniasis. Geotechnological tools allow the analysis and recognition of spatiotemporal patterns by monitoring and mapping risk areas of this vector-borne disease. This study aims to describe the sandfly fauna in the municipality of Corumbá and to compare it with the data described in a three-year period from 1984 to 1986 by Galati. A further aim was to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 43 publications
4
40
1
Order By: Relevance
“…Six studies on human VL found a direct association between vegetation cover and risk of VL 16,18,19,29,39,40 , while only one found an inverse association 41 . In the studies on vectors, two found higher vector density in areas with little vegetation cover 34,35 and one found a direct relationship between vegetation cover and presence of vectors 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies on human VL found a direct association between vegetation cover and risk of VL 16,18,19,29,39,40 , while only one found an inverse association 41 . In the studies on vectors, two found higher vector density in areas with little vegetation cover 34,35 and one found a direct relationship between vegetation cover and presence of vectors 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Only two of these studies addressed the association between environmental features extracted from satellite images and canine VL 34,38 . An ecological study in 33 municipalities in Bahia State, by Bavia et al 38 , found an inverse association between vegetation cover and cases of canine VL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique has been widely employed in the study of leishmaniasis and has permitted detailed analyses of the spatial dependency between canine and human VL, the distribution of the vector, and the characterization of areas with high incidence and high risk of morbidity [7,[18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%